2020
DOI: 10.1177/2158244020941001
|View full text |Cite
|
Sign up to set email alerts
|

An Appraisal of Production Subcontracting Toward Small and Medium Scale Enterprises Development in the Nigeria Industrial Sector: A Review Approach

Abstract: This paper is an appraisal of production subcontracting and how it stimulates the survival of small and medium scale enterprises (SMEs) in the Nigeria industrial sector. The aim of this article is to extend the debate on the desirability of production subcontracting between SMEs and its relevance to industrial development policy in Nigeria. The analysis in this paper was based on a desktop review of 15 articles published in Nigeria on production subcontracting and SMEs within a 19-year period (2001–20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Nwokocha et al (2019) found that the subcontracting relationship between large-scale industries and small businesses is inclined to production and product-related cooperation, where the contractors are concerned with meeting fluctuation in demand and shortening long delivery times. According to Nwokocha et al (2020), production subcontracting strategy is instrumental in the survival of small businesses in the industrial sector, given the ability to guarantee reductions in operating costs and risk, and resources' accessibility.…”
Section: Impact On Revenuesmentioning
confidence: 99%
“…Nwokocha et al (2019) found that the subcontracting relationship between large-scale industries and small businesses is inclined to production and product-related cooperation, where the contractors are concerned with meeting fluctuation in demand and shortening long delivery times. According to Nwokocha et al (2020), production subcontracting strategy is instrumental in the survival of small businesses in the industrial sector, given the ability to guarantee reductions in operating costs and risk, and resources' accessibility.…”
Section: Impact On Revenuesmentioning
confidence: 99%